Newcastle disease virus: macromolecules and opportunities - Yusoff, Khatijah; Tan, Wen Siang (Taylor & Francis, 2001)
Over the past two decades, enormous advances have occurred in the structural and biological characterization of Newcastle disease virus (NDV). As a result, not only the complete sequence of the viral genome has been fully determined, but also a clearer understanding of the viral proteins and their respective roles in the life cycle has been achieved. This article reviews the progress in the molecular biology of NDV with emphasis on the new technologies. It also identifies the fundamental problems that need to be addressed and attempts to predict some research opportunities in NDV that can be realized in the near future for the diagnosis, prevention and treatment of disease(s).